The Effect of Noise on Hearing Loss and Blood Pressure of Workers in a Steel Industry in the Southwest of Iran - hossein ali Rangkooy; payam Rashnoudi; Arman Amiri; zohreh shabgard (Shahid Sadoughi University of Medical Sciences, 2022)
Introduction: Today, it is well-established that, in addition to hearing loss, noise affects the natural physiological functions of the body. The aim of this study was to determine the effect of noise on hearing loss and blood pressure in workers of a steel industry in southwest of Iran. Methods: This study was performed on 54 steel workers. Dosimetry was performed using TES 1358 sound meter and Beurer BC16 blood pressure monitor, respectively. Statistical analysis was done using SPSS 24 software at the significant level of 0.05. Results: There was a significant relationship between hearing loss and sound pressure level in each of the case and control groups (P< 0.05). Despite the significant relationship between hearing loss and age, (P˂0.05), there was no significant relationship between the work experience variable and hearing loss (P> 0.05). Age and work experience had a significant relationship with hearing loss at some frequencies under the study (P˂0.05). There was also a significant difference between the mean of blood pressure in the case and control group (P˂0.05). Conclusion: The results of this study indicated that exposure to noise increased blood pressure in individuals and the effects of exposure intensified with age. Therefore, control measures such as reducing sound pressure level, training programs and regular screening of the workers' blood pressure are recommended to reduce the effects of noise.